A review of the subgenus Delineatia Volynkin & Huang, 2019 of the genus Ammatho Walker, 1855, with descriptions of two new species from Taiwan and Vietnam (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; Wu, Shipher (Zootaxa, 2020)
The subgenus Delineatia Volynkin & Huang, 2019 of the genus Ammatho Walker, 1855 is reviewed. The subgenus is subdivided into the A. delineata and the A. sublucana species-groups. Two new species are described: Ammatho (Delineatia) tairadiata Wu & Volynkin, sp. n. from Taiwan and Ammatho (Delineatia) trangchim Volynkin &Wu, sp. n. from Central Vietnam. The synonymy of Hypocrita rhodina Herrich-Schäffer, 1855 with Ammatho (Delineatia) delineata (Walker, 1854) is revised. It is stated that the type locality of H. rhodina, Borneo is wrong and probably based on the incorrectly labeled type specimen. Adults and male and female genitalia of all species are illustrated.